Women Deprivation Index and Family Planning Utilisation in Urban Geography of West African Countries - Akinyemi, Akanni Ibukun; Mobolaji, Jacob Wale; Abe, John Olugbenga; Ibrahim, Elhakim; Ikuteyijo, Olutoyin (Frontiers in Global Women's Health, 2021)
Inequalities in health care utilisation and outcomes vary significantly across geographies. Though available evidence suggests disparity in contraceptive uptake in favour of urban compared with rural geographies, there are unassessed nuances among women in urban communities. This study examines some of these disparities within the context of socioeconomic deprivations and family planning utilisation among urban women in West Africa. A secondary analysis of the most recent Demographic and Health Survey dataset of five selected West African countries was conducted, using pooled data of 21,641 women aged 15–49 years. Associations between family planning utilisation and women's deprivation status were investigated using a binary logistic regression model. The findings show that more than one-quarter of the women were severely deprived across the countries except Senegal (17.4%), and the severely deprived consistently have relatively low contraceptive prevalence rates (CPR) (16.0–24.3%) compared with women with no/low deprivation across the countries except Senegal (39.8%). The results for long-acting reversible contraceptives (LARC) were not consistent across the five countries: whereas, LARC utilisation was lower among severely deprived women in Nigeria (9.1%), Guinea (9.6%), and Mali (19.3%), utilisation was similar across the deprivation groups in Benin and Senegal. In the multivariable analyses, the log-odds of modern contraceptive utilisation decreases by 0.27 among the moderately deprived (ß = −0.27, SE = 0.05, p < 0.01) and by 0.75 among the severely deprived women (ß = −0.75, SE = 0.05, p < 0.01) compared with those with no/low deprivation, with variations across the countries. Similarly, the log-odds of LARC utilisation decreases by 0.44–0.72 among the severely deprived women compared with those with no/low deprivation across the countries except Senegal. This study concluded that family planning intervention programmes and policies need to underscore the deprivation context of urban geographies, particularly among women living in informal settlements.